Graphene conductive film and preparation method thereof
By adding reinforcement resin, conductive reinforcement filler and isocyanate to the preparation of graphene conductive films, and forming a semi-interpenetrating cross-linking network, the problem of degradation of the conductive films after long-term use is solved, achieving higher aging resistance and mechanical properties, while improving the conductive properties.
Patent Information
- Application Number
- CN202510375369.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
After long-term use of existing graphene conductive films, their flexibility and conductivity will decrease, affecting the normal operation of material devices.
The mechanical and conductive properties of the film are enhanced by adding reinforcement resin, conductive reinforcement filler and isocyanate when preparing the graphene conductive film, and using a catalyst during the mixing and stirring process.
It effectively solves the problem of degradation of flexibility and conductivity after long-term use of conductive films, improves the aging resistance and mechanical properties of the films, and enhances the conductive properties.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive films, and in particular to a graphene conductive film and a preparation method thereof. Background Art
[0002] With the development of science and technology, the rise of smart consumer electronics and wearable electronics has attracted people's attention. Among them, conductive films are deeply loved by the market due to their unique properties. Graphene conductive films are made of graphene as conductive filler and polymer as matrix. With the long-term use of material devices, repeated external force loading-unloading process will lead to crystallization of polymer and structural separation of graphene and polymer. At the same time, long-term light and oxygen will cause the polymer molecular chain to break and oxidize respectively, which will cause the flexibility and conductivity of the conductive film to decrease, thereby affecting the normal operation of the material device. Summary of the invention
[0003] The purpose of the present invention is to provide a graphene conductive film and a preparation method thereof. By adding reinforcing resin, conductive reinforcing filler and isocyanate, the problem of decreased flexibility and conductivity of the existing conductive film after long-term use is solved. At the same time, due to its special rotaxane structure, the conductive film has certain aging resistance.
[0004] The object of the present invention can be achieved by the following technical scheme: a method for preparing a graphene conductive film, comprising the following steps: weighing the following raw materials in parts by weight: 6-7 parts of graphene powder, 50-60 parts of reinforcing resin, 1.5-1.8 parts of conductive reinforcing filler, 5-6 parts of hexamethylene diisocyanate, 0.1-0.2 parts of catalyst, 2-3 parts of compatibilizer, 1.2-1.5 parts of defoamer, 0.8-1 parts of plasticizer, 0.8-1 parts of antioxidant and 12-15 parts of water; mixing the graphene powder, reinforcing resin, conductive reinforcing filler, hexamethylene diisocyanate, catalyst, compatibilizer, defoamer, plasticizer, antioxidant and water, stirring for 10 minutes at a temperature of 65°C, coating and drying to obtain a graphene conductive film; The graphene powder is Gefit 8415 graphene powder; The catalyst is Longchi T-12 catalyst; The compatibilizer is Dow Corning OFS-6020; The defoamer is Longdi XH82 defoamer; The plasticizer is Blue Sail DOS plasticizer; The antioxidant is DuPont 3185 antioxidant.
[0005] The reinforced resin is prepared by the following steps: Step A1: ferrocenecarboxamide, 2,5-dimethoxytetrahydrofuran and glacial acetic acid are mixed, and the mixture is reacted for 5-6 hours at a stirring rate of 160-180 rpm and a temperature of 100° C., and then cooled to room temperature to obtain a capped monomer; The dosage ratio of ferrocenecarboxamide, 2,5-dimethoxytetrahydrofuran and glacial acetic acid is 0.03-0.035 mol: 0.035-0.038 mol: 40-45 mL; During the reaction, the primary amine group in ferrocenecarboxamide reacts with 2,5-dimethoxytetrahydrofuran through the Clauson-Kaas synthesis method to form an N-substituted pyrrole structure to obtain a capping monomer.
[0006] Step A2: β-cyclodextrin and deionized water are mixed, stirred at a stirring rate of 180-200 rpm and a temperature of 40° C., pyrrole is added, stirred for 4-6 hours, then cooled to 5° C., and then under ultrasonic dispersion conditions, ferric chloride solution and ethanol are added, stirred, reacted for 6-8 hours, and then a capping monomer is added, and the reaction is continued for 12 hours to obtain a polyrotaxane; The mass concentration of ferric chloride solution is 0.1g / mL, and the ratio of β-cyclodextrin, pyrrole, ferric chloride solution and end-capping monomer is 23-24g: 0.03-0.04mol: 30-35mL: 0.001-0.0012mol; During the reaction, β-cyclodextrin and pyrrole are first mixed in deionized water and ultrasonically dispersed. Due to the host-guest inclusion complex between β-cyclodextrin and pyrrole, pyrrole enters the cavity of β-cyclodextrin. Then, ferric chloride solution is added to form a linear polypyrrole structure through oxidative polymerization, and a capping monomer is added to react and cap the end, forming a rotaxane structure with polypyrrole as the axis and passing through the cavity of β-cyclodextrin, thereby obtaining a polyrotaxane.
[0007] Step A3: Mix the polyrotaxane and sodium hydroxide solution, stir at a stirring rate of 140-160 rpm and a temperature of 5°C, add propylene oxide, and react for 12 hours to obtain a modified polyrotaxane; mix the modified polyrotaxane and caprolactone, stir at a stirring rate of 180-240 rpm and a temperature of 100°C, add stannous octoate, and react for 4-6 hours to obtain a reinforced resin; The molar concentration of the sodium hydroxide solution is 1 mol / L, the amount ratio of the polyrotaxane, the sodium hydroxide solution and propylene oxide is 1.4-1.6 g: 110-120 mL: 0.11-0.12 mol; the amount ratio of the modified polyrotaxane, caprolactone and stannous octoate is 1.5-1.6 g: 14-15 mL: 0.2-0.3 mL; During the reaction, under alkaline conditions, the hydroxyl group in β-cyclodextrin in the polyrotaxane reacts with the epoxy group in propylene oxide to form a hydroxymethyl structure to obtain a modified polyrotaxane. Under the action of stannous octoate, the hydroxymethyl structure in the modified polyrotaxane reacts with caprolactone to introduce a caprolactone chain segment to obtain a reinforced resin.
[0008] The conductive reinforcing filler is prepared by the following steps: Step B1: Carboxylated carbon nanotubes and thionyl chloride were mixed and ultrasonically dispersed for 30 minutes, and reacted for 24 hours at a stirring rate of 120-140 rpm and a temperature of 90°C to obtain a precursor 1. Precursor 1, copper tetraaminophthalocyanine and N,N-dimethylformamide were mixed and ultrasonically dispersed for 15 minutes, and triethylamine was added under stirring at a stirring rate of 160-180 rpm and a temperature of 100°C, and reacted for 24 hours to obtain a precursor 2; The ratio of carboxylated carbon nanotubes to thionyl chloride is 0.4-0.5 g: 60-80 mL; the ratio of precursor 1, copper tetraaminophthalocyanine and triethylamine is 0.35-0.38 g: 0.07-0.08 g: 0.3-0.4 mL; During the reaction, under the action of thionyl chloride, the carboxyl groups on the carboxylated carbon nanotubes are chlorinated to form acyl chloride groups, thereby obtaining precursor 1. Then, under the action of triethylamine, the acyl chloride groups in precursor 1 react with the amino groups in tetraaminophthalocyanine copper to form amide groups, thereby obtaining precursor 2.
[0009] Step B2: tri(4-bromophenyl)amine, 4-formylphenylboronic acid and tetrahydrofuran are mixed, and potassium carbonate solution and bistriphenylphosphine palladium dichloride are added under stirring at a rate of 160-180 rpm and a temperature of 65°C, and the mixture is reacted for 12 hours to obtain intermediate a. Intermediate a, copper tetraaminophthalocyanine, precursor 2 and N,N-dimethylformamide are mixed and ultrasonically dispersed for 20 minutes, and the mixture is reacted for 24 hours under stirring at a rate of 120-140 rpm and a temperature of 120°C to obtain a conductive reinforcing filler; The molar concentration of potassium carbonate solution is 2 mol / L, the dosage ratio of tri(4-bromophenyl)amine, 4-formylphenylboric acid, potassium carbonate solution and bistriphenylphosphine palladium dichloride is 0.001-0.0011 mol: 0.0035 mol: 25-30 mL: 0.3-0.4 g; the dosage ratio of intermediate a, tetraaminophthalocyanine copper and precursor 2 is 0.24-0.26 g: 0.28-0.3 g: 0.3 g; During the reaction, under the condition of bistriphenylphosphine palladium dichloride as a catalyst, bromine in tri(4-bromophenyl)amine reacts with the boric acid group in 4-formylphenylboronic acid to obtain an intermediate a containing a formyl group, and the formyl group in the intermediate a reacts with the amino group in the precursor 2 and the amino group in tetraaminophthalocyanine copper to form a Schiff base structure. At the same time, due to the π-π interaction between the precursor 2 and the phthalocyanine structure, the surface of the precursor 2 is loaded with copper phthalocyanine polymers to obtain a conductive reinforcing filler.
[0010] Beneficial effects of the invention: The invention discloses a graphene conductive film and a preparation method thereof, which solves the problem of the decrease in flexibility and conductivity of the existing conductive film after long-term use by adding reinforcing resin, conductive reinforcing filler and isocyanate. At the same time, due to its special rotaxane structure, it has certain aging resistance. During the mixing and stirring of the raw materials, due to the presence of the catalyst, the isocyanate group in hexamethylene diisocyanate can react with the terminal hydroxyl group in the branch chain of the reinforcing resin, and can also react with the unreacted amino group in the conductive reinforcing filler, thereby forming a semi-interpenetrating cross-linked network with hexamethylene diisocyanate as a cross-linking agent. Since the reinforcing resin itself is a rotaxane structure with polypyrrole as the axis and passing through the cavity of β-cyclodextrin, the presence of the polypyrrole axis and the terminal ferrocene makes the conductive film have good dielectric properties, and the rotaxane structure makes the conductive film exhibit better mechanical properties when subjected to external forces, and since it is connected to the conductive reinforcing filler by covalent bonds, the conductive film can conduct force to the conductive reinforcing filler when subjected to external forces, thereby further improving the mechanical properties of the conductive film, and the conductive reinforcing filler itself is based on carbon nanotubes, and the surface is loaded with copper phthalocyanine oligomers containing Schiff base structures by covalent bonds and π-π effects. The presence of this structure makes its conductive reinforcing filler have good conductive properties, and its structure cooperates with layered graphene, further improving the conductive properties of the conductive film. DETAILED DESCRIPTION
[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0012] Embodiment 1 A method for preparing a graphene conductive film comprises the following steps: weighing the following raw materials in parts by weight: 6 parts of graphene powder, 50 parts of reinforcing resin, 1.5 parts of conductive reinforcing filler, 5 parts of hexamethylene diisocyanate, 0.1 parts of catalyst, 2 parts of compatibilizer, 1.2 parts of defoamer, 0.8 parts of plasticizer, 0.8 parts of antioxidant and 12 parts of water; mixing the graphene powder, reinforcing resin, conductive reinforcing filler, hexamethylene diisocyanate, catalyst, compatibilizer, defoamer, plasticizer, antioxidant and water, stirring for 10 minutes at a temperature of 65° C., coating and drying to obtain a graphene conductive film; The graphene powder is Gefit 8415 graphene powder; The catalyst is Longchi T-12 catalyst; The compatibilizer is Dow Corning OFS-6020; The defoamer is Longdi XH82 defoamer; The plasticizer is Blue Sail DOS plasticizer; The antioxidant is DuPont 3185 antioxidant; The reinforced resin is prepared by the following steps: Step A1: ferrocenecarboxamide, 2,5-dimethoxytetrahydrofuran and glacial acetic acid were mixed, and the mixture was reacted for 5 hours at a stirring rate of 160 rpm and a temperature of 100° C., and then cooled to room temperature to obtain a capped monomer; The dosage ratio of ferrocenecarboxamide, 2,5-dimethoxytetrahydrofuran and glacial acetic acid is 0.03 mol: 0.035 mol: 40 mL; Step A2: β-cyclodextrin and deionized water were mixed, and pyrrole was added under stirring at a stirring rate of 180 rpm and a temperature of 40°C, and stirred for 4 hours, and then the temperature was lowered to 5°C, and then ferric chloride solution and ethanol were added under stirring under ultrasonic dispersion conditions, and the reaction was carried out for 6 hours, and then the end-capping monomer was added, and the reaction was continued for 12 hours to obtain a polyrotaxane; The mass concentration of ferric chloride solution is 0.1 g / mL, and the ratio of β-cyclodextrin, pyrrole, ferric chloride solution and end-capping monomer is 23 g: 0.03 mol: 30 mL: 0.001 mol; Step A3: Mix the polyrotaxane and sodium hydroxide solution, stir at a stirring rate of 140 rpm and a temperature of 5°C, add propylene oxide, and react for 12 hours to obtain a modified polyrotaxane; mix the modified polyrotaxane and caprolactone, stir at a stirring rate of 180 rpm and a temperature of 100°C, add stannous octoate, and react for 4 hours to obtain a reinforced resin; The molar concentration of the sodium hydroxide solution is 1 mol / L, the amount ratio of polyrotaxane, sodium hydroxide solution and propylene oxide is 1.4 g: 110 mL: 0.11 mol; the amount ratio of modified polyrotaxane, caprolactone and stannous octoate is 1.5 g: 14 mL: 0.2 mL; The conductive reinforcing filler is prepared by the following steps: Step B1: Mix Hongwu MW01 carboxylated carbon nanotubes and thionyl chloride and ultrasonically disperse them for 30 minutes, react at a stirring rate of 120 rpm and a temperature of 90°C for 24 hours to obtain precursor 1, mix precursor 1, copper tetraaminophthalocyanine and N,N-dimethylformamide and ultrasonically disperse them for 15 minutes, stir at a stirring rate of 160-180 rpm and a temperature of 100°C and add triethylamine, and react for 24 hours to obtain precursor 2; The ratio of carboxylated carbon nanotubes to thionyl chloride was 0.4 g:60 mL; the ratio of precursor 1, copper tetraaminophthalocyanine and triethylamine was 0.35 g:0.07 g:0.3 mL; Step B2: tri(4-bromophenyl)amine, 4-formylphenylboronic acid and tetrahydrofuran were mixed, and potassium carbonate solution and bistriphenylphosphine palladium dichloride were added under stirring at a rate of 160 rpm and a temperature of 65°C, and the mixture was reacted for 12 hours to obtain intermediate a. Intermediate a, copper tetraaminophthalocyanine, precursor 2 and N,N-dimethylformamide were mixed and ultrasonically dispersed for 20 minutes, and the mixture was reacted for 24 hours under stirring at a rate of 120 rpm and a temperature of 120°C to obtain a conductive reinforcing filler; The molar concentration of potassium carbonate solution is 2 mol / L, the dosage ratio of tri(4-bromophenyl)amine, 4-formylphenylboric acid, potassium carbonate solution and bistriphenylphosphine palladium dichloride is 0.001 mol: 0.0035 mol: 25 mL: 0.3 g; the dosage ratio of intermediate a, tetraaminophthalocyanine copper and precursor 2 is 0.24 g: 0.28 g: 0.3 g.
[0013] Embodiment 2 A method for preparing a graphene conductive film comprises the following steps: weighing the following raw materials in parts by weight: 7 parts of graphene powder, 50 parts of reinforcing resin, 1.8 parts of conductive reinforcing filler, 5 parts of hexamethylene diisocyanate, 0.2 parts of catalyst, 2 parts of compatibilizer, 1.2 parts of defoamer, 1 part of plasticizer, 0.8 parts of antioxidant and 15 parts of water; mixing the graphene powder, reinforcing resin, conductive reinforcing filler, hexamethylene diisocyanate, catalyst, compatibilizer, defoamer, plasticizer, antioxidant and water, stirring for 10 minutes at a temperature of 65°C, coating and drying to obtain a graphene conductive film; The graphene powder is Gefit 8415 graphene powder; The catalyst is Longchi T-12 catalyst; The compatibilizer is Dow Corning OFS-6020; The defoamer is Longdi XH82 defoamer; The plasticizer is Blue Sail DOS plasticizer; The antioxidant is DuPont 3185 antioxidant; The reinforced resin is prepared by the following steps: Step A1: ferrocenecarboxamide, 2,5-dimethoxytetrahydrofuran and glacial acetic acid were mixed, and the mixture was reacted for 6 hours at a stirring rate of 160 rpm and a temperature of 100° C., and then cooled to room temperature to obtain a capped monomer; The dosage ratio of ferrocenecarboxamide, 2,5-dimethoxytetrahydrofuran and glacial acetic acid is 0.03 mol: 0.035 mol: 45 mL; Step A2: β-cyclodextrin and deionized water were mixed, and pyrrole was added under stirring at a stirring rate of 200 rpm and a temperature of 40°C, and stirred for 4 hours, and then the temperature was lowered to 5°C, and then ferric chloride solution and ethanol were added under stirring under ultrasonic dispersion conditions, and the reaction was carried out for 6 hours, and then the end-capping monomer was added, and the reaction was continued for 12 hours to obtain a polyrotaxane; The mass concentration of ferric chloride solution is 0.1 g / mL, and the ratio of β-cyclodextrin, pyrrole, ferric chloride solution and end-capping monomer is 24 g: 0.03 mol: 30 mL: 0.0012 mol; Step A3: Mix the polyrotaxane and sodium hydroxide solution, stir at a stirring rate of 140 rpm and a temperature of 5°C, add propylene oxide, and react for 12 hours to obtain a modified polyrotaxane; mix the modified polyrotaxane and caprolactone, stir at a stirring rate of 240 rpm and a temperature of 100°C, add stannous octoate, and react for 4 hours to obtain a reinforced resin; The molar concentration of the sodium hydroxide solution is 1 mol / L, the amount ratio of polyrotaxane, sodium hydroxide solution and propylene oxide is 1.4 g: 120 mL: 0.12 mol; the amount ratio of modified polyrotaxane, caprolactone and stannous octoate is 1.5 g: 14 mL: 0.3 mL; The conductive reinforcing filler is prepared by the following steps: Step B1: Mix Hongwu MW01 carboxylated carbon nanotubes and thionyl chloride and ultrasonically disperse them for 30 minutes, react at a stirring rate of 140 rpm and a temperature of 90°C for 24 hours to obtain precursor 1, mix precursor 1, copper tetraaminophthalocyanine and N,N-dimethylformamide and ultrasonically disperse them for 15 minutes, stir at a stirring rate of 160 rpm and a temperature of 100°C and add triethylamine, react for 24 hours to obtain precursor 2; The ratio of carboxylated carbon nanotubes to thionyl chloride was 0.5 g:60 mL; the ratio of precursor 1, copper tetraaminophthalocyanine and triethylamine was 0.38 g:0.07 g:0.3 mL; Step B2: tri(4-bromophenyl)amine, 4-formylphenylboronic acid and tetrahydrofuran were mixed, and potassium carbonate solution and bistriphenylphosphine palladium dichloride were added under stirring at a rate of 180 rpm and a temperature of 65°C, and the mixture was reacted for 12 hours to obtain intermediate a. Intermediate a, copper tetraaminophthalocyanine, precursor 2 and N,N-dimethylformamide were mixed and ultrasonically dispersed for 20 minutes, and the mixture was reacted for 24 hours under stirring at a rate of 120 rpm and a temperature of 120°C to obtain a conductive reinforcing filler; The molar concentration of potassium carbonate solution is 2 mol / L, the dosage ratio of tri(4-bromophenyl)amine, 4-formylphenylboric acid, potassium carbonate solution and bistriphenylphosphine palladium dichloride is 0.0011 mol: 0.0035 mol: 25 mL: 0.3 g; the dosage ratio of intermediate a, tetraaminophthalocyanine copper and precursor 2 is 0.24 g: 0.3 g: 0.3 g.
[0014] Embodiment 3 A method for preparing a graphene conductive film comprises the following steps: weighing the following raw materials in parts by weight: 7 parts of graphene powder, 60 parts of reinforcing resin, 1.8 parts of conductive reinforcing filler, 6 parts of hexamethylene diisocyanate, 0.2 parts of catalyst, 3 parts of compatibilizer, 1.5 parts of defoamer, 1 part of plasticizer, 1 part of antioxidant and 15 parts of water; mixing the graphene powder, reinforcing resin, conductive reinforcing filler, hexamethylene diisocyanate, catalyst, compatibilizer, defoamer, plasticizer, antioxidant and water, stirring for 10 minutes at a temperature of 65°C, coating and drying to obtain a graphene conductive film; The graphene powder is Gefit 8415 graphene powder; The catalyst is Longchi T-12 catalyst; The compatibilizer is Dow Corning OFS-6020; The defoamer is Longdi XH82 defoamer; The plasticizer is Blue Sail DOS plasticizer; The antioxidant is DuPont 3185 antioxidant; The reinforced resin is prepared by the following steps: Step A1: ferrocenecarboxamide, 2,5-dimethoxytetrahydrofuran and glacial acetic acid were mixed, stirred at a rate of 180 rpm and a temperature of 100° C. for 6 h, and then cooled to room temperature to obtain a capped monomer; The dosage ratio of ferrocenecarboxamide, 2,5-dimethoxytetrahydrofuran and glacial acetic acid is 0.035mol:0.038mol:45mL; Step A2: β-cyclodextrin and deionized water were mixed, and pyrrole was added under stirring at a stirring rate of 200 rpm and a temperature of 40°C, and stirred for 6 hours, and then the temperature was lowered to 5°C, and then ferric chloride solution and ethanol were added under stirring under ultrasonic dispersion conditions, and the reaction was carried out for 8 hours, and then the end-capping monomer was added, and the reaction was continued for 12 hours to obtain a polyrotaxane; The mass concentration of ferric chloride solution is 0.1 g / mL, and the ratio of β-cyclodextrin, pyrrole, ferric chloride solution and end-capping monomer is 24 g: 0.04 mol: 35 mL: 0.0012 mol; Step A3: Mix the polyrotaxane and sodium hydroxide solution, stir at a stirring rate of 160 rpm and a temperature of 5°C, add propylene oxide, and react for 12 hours to obtain a modified polyrotaxane; mix the modified polyrotaxane and caprolactone, stir at a stirring rate of 240 rpm and a temperature of 100°C, add stannous octoate, and react for 6 hours to obtain a reinforced resin; The molar concentration of the sodium hydroxide solution is 1 mol / L, the amount ratio of polyrotaxane, sodium hydroxide solution and propylene oxide is 1.6 g: 120 mL: 0.12 mol; the amount ratio of modified polyrotaxane, caprolactone and stannous octoate is 1.6 g: 15 mL: 0.3 mL; The conductive reinforcing filler is prepared by the following steps: Step B1: Mix Hongwu MW carboxylated carbon nanotubes and thionyl chloride and ultrasonically disperse them for 30 minutes, react for 24 hours at a stirring rate of 140 rpm and a temperature of 90°C to obtain precursor 1, mix precursor 1, tetraaminophthalocyanine copper and N,N-dimethylformamide and ultrasonically disperse them for 15 minutes, stir and add triethylamine at a stirring rate of 180 rpm and a temperature of 100°C, and react for 24 hours to obtain precursor 2; The ratio of carboxylated carbon nanotubes to thionyl chloride is 0.5 g:80 mL; the ratio of precursor 1, copper tetraaminophthalocyanine and triethylamine is 0.38 g:0.08 g:0.4 mL; Step B2: tri(4-bromophenyl)amine, 4-formylphenylboronic acid and tetrahydrofuran were mixed, and potassium carbonate solution and bistriphenylphosphine palladium dichloride were added under stirring at a rate of 180 rpm and a temperature of 65°C, and the mixture was reacted for 12 hours to obtain intermediate a. Intermediate a, copper tetraaminophthalocyanine, precursor 2 and N,N-dimethylformamide were mixed and ultrasonically dispersed for 20 minutes, and the mixture was reacted for 24 hours under stirring at a rate of 140 rpm and a temperature of 120°C to obtain a conductive reinforcing filler; The molar concentration of potassium carbonate solution is 2 mol / L, the dosage ratio of tri(4-bromophenyl)amine, 4-formylphenylboric acid, potassium carbonate solution and bistriphenylphosphine palladium dichloride is 0.0011 mol: 0.0035 mol: 25 mL: 0.4 g; the dosage ratio of intermediate a, tetraaminophthalocyanine copper and precursor 2 is 0.26 g: 0.3 g: 0.3 g.
[0015] Comparative Example 1 Compared with Example 3, this comparative example is different in that the reinforcing resin in the preparation process of the graphene conductive film in Example 3 is replaced by the polyrotaxane in Example 3, and the other steps are the same.
[0016] Comparative Example 2 Compared with Example 3, this comparative example replaces the reinforcing resin in the preparation process of the graphene conductive film in Example 3 with a mixture of Shenhua POW polypyrrole and SiChuang 4451 polycaprolactone, and the weight ratio of polypyrrole to polycaprolactone is 1.2g:0.4g.
[0017] Comparative Example 3 Compared with Example 3, this comparative example is different in that the conductive reinforcing filler in the preparation process of the graphene conductive film in Example 3 is replaced with Hongwu MW carboxylated carbon nanotubes, and the other steps are the same.
[0018] Take the graphene conductive films prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, refer to GB / T 1040.3-2006, cut them into dumbbell-shaped type 5 samples, use a universal mechanical testing machine, and test their mechanical properties at a tensile rate of 100 mm / min. Use a dual-electric four-probe tester to test the conductivity of the sample under static conditions. The sample size is 10 mm×10 mm. The sample is repeatedly bent 100 times and aged in a UV aging box for 3 days. Then, its conductivity is tested and its performance retention rate is calculated. Performance retention rate=conductivity after aging / conductivity before aging*100%. The test results are shown in Table 1 below: Table 1 Test results Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Elongation at break (%) 239 242 254 217 183 248 Conductivity (S / cm) 8.46 8.55 8.59 8.17 8.34 6.51 Performance retention rate (%) 99.82 99.83 99.84 99.75 98.42 97.54 It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3, the reinforcing resin in the preparation process of the graphene conductive film of Example 3 is replaced by the polyrotaxane of Example 3. Due to the lack of side chains, the performance of Comparative Example 1 is reduced. The reinforcing resin in the preparation process of the graphene conductive film of Example 3 is replaced by a mixture of polypyrrole and polycaprolactone. Due to the lack of a polyrotaxane structure, the performance of Comparative Example 2 is replaced by a mixture of polypyrrole and polycaprolactone. Due to the lack of a polyrotaxane structure, the performance of Comparative Example 3 is replaced by a conductive reinforcing filler in the preparation process of the graphene conductive film of Example 3 with carboxylated carbon nanotubes. Due to the lack of copper phthalocyanine oligomers, the performance of Comparative Example 3 is reduced.
[0019] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0020] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a graphene conductive film, characterized in that: The method comprises the following steps: weighing the following raw materials in parts by weight: 6-7 parts of graphene powder, 50-60 parts of reinforcing resin, 1.5-1.8 parts of conductive reinforcing filler, 5-6 parts of hexamethylene diisocyanate, 0.1-0.2 parts of catalyst, 2-3 parts of compatibilizer, 1.2-1.5 parts of defoamer, 0.8-1 parts of plasticizer, 0.8-1 parts of antioxidant and 12-15 parts of water; mixing the graphene powder, reinforcing resin, conductive reinforcing filler, hexamethylene diisocyanate, catalyst, compatibilizer, defoamer, plasticizer, antioxidant and water, stirring for 10 minutes at a temperature of 65°C, coating and drying to obtain a graphene conductive film; The reinforced resin is prepared by the following steps: Step A1: ferrocenecarboxamide, 2,5-dimethoxytetrahydrofuran and glacial acetic acid are mixed, and the mixture is reacted for 5-6 hours at a stirring rate of 160-180 rpm and a temperature of 100° C., and then cooled to room temperature to obtain a capped monomer; Step A2: β-cyclodextrin and deionized water are mixed, stirred at a stirring rate of 180-200 rpm and a temperature of 40° C., pyrrole is added, stirred for 4-6 hours, then cooled to 5° C., and then under ultrasonic dispersion conditions, ferric chloride solution and ethanol are added, stirred, reacted for 6-8 hours, and then a capping monomer is added, and the reaction is continued for 12 hours to obtain a polyrotaxane; Step A3: Mix the polyrotaxane and sodium hydroxide solution, stir at a stirring rate of 140-160 rpm and a temperature of 5°C, add propylene oxide, and react for 12 hours to obtain a modified polyrotaxane; mix the modified polyrotaxane and caprolactone, stir at a stirring rate of 180-240 rpm and a temperature of 100°C, add stannous octoate, and react for 4-6 hours to obtain a reinforced resin; The conductive reinforcing filler is prepared by the following steps: Step B1: Carboxylated carbon nanotubes and thionyl chloride were mixed and ultrasonically dispersed for 30 minutes, and reacted for 24 hours at a stirring rate of 120-140 rpm and a temperature of 90°C to obtain a precursor 1. Precursor 1, copper tetraaminophthalocyanine and N,N-dimethylformamide were mixed and ultrasonically dispersed for 15 minutes, and triethylamine was added under stirring at a stirring rate of 160-180 rpm and a temperature of 100°C, and reacted for 24 hours to obtain a precursor 2; Step B2: tri(4-bromophenyl)amine, 4-formylphenylboronic acid and tetrahydrofuran are mixed, and potassium carbonate solution and bistriphenylphosphine palladium dichloride are added under stirring at a rate of 160-180 rpm and a temperature of 65°C, and the reaction is carried out for 12 hours to obtain intermediate a. Intermediate a, copper tetraaminophthalocyanine, precursor 2 and N,N-dimethylformamide are mixed and ultrasonically dispersed for 20 minutes, and the reaction is carried out for 24 hours under stirring at a rate of 120-140 rpm and a temperature of 120°C to obtain a conductive reinforcing filler.
2. The method for preparing a graphene conductive film according to claim 1, characterized in that: In step A1, the ratio of ferrocenecarboxamide, 2,5-dimethoxytetrahydrofuran and glacial acetic acid is 0.03-0.035 mol: 0.035-0.038 mol: 40-45 mL.
3. The method for preparing a graphene conductive film according to claim 1, characterized in that: In step A2: the mass concentration of the ferric chloride solution is 0.1 g / mL, and the amount ratio of β-cyclodextrin, pyrrole, ferric chloride solution and end-capping monomer is 23-24 g: 0.03-0.04 mol: 30-35 mL: 0.001-0.0012 mol.
4. The method for preparing a graphene conductive film according to claim 1, characterized in that: In step A3: the molar concentration of the sodium hydroxide solution is 1 mol / L, the amount ratio of the polyrotaxane, the sodium hydroxide solution and the propylene oxide is 1.4-1.6 g: 110-120 mL: 0.11-0.12 mol; the amount ratio of the modified polyrotaxane, caprolactone and stannous octoate is 1.5-1.6 g: 14-15 mL: 0.2-0.3 mL.
5. The method for preparing a graphene conductive film according to claim 1, characterized in that: In step B1, the ratio of carboxylated carbon nanotubes to thionyl chloride is 0.4-0.5 g: 60-80 mL; the ratio of precursor 1, copper tetraaminophthalocyanine and triethylamine is 0.35-0.38 g: 0.07-0.08 g: 0.3-0.4 mL.
6. The method for preparing a graphene conductive film according to claim 1, characterized in that: In step B2: the molar concentration of potassium carbonate solution is 2 mol / L, the amount ratio of tri(4-bromophenyl)amine, 4-formylphenylboric acid and potassium carbonate solution and bistriphenylphosphine palladium dichloride is 0.001-0.0011 mol: 0.0035 mol: 25-30 mL: 0.3-0.4 g; the amount ratio of intermediate a, tetraaminophthalocyanine copper and precursor 2 is 0.24-0.26 g: 0.28-0.3 g: 0.3 g.
7. A graphene conductive film, characterized in that: Prepared according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of polypyrrole / cyclodextrin pseudopolyrotaxane molecular wire
CN101798359A
Preparation method and application of graphene / carbon nanotube composite slurry
CN118387863A
Low-voltage power cable
CN118571538A
Cited By
Electro-catalysis filter membrane for removing bromate in water, preparation method, device and application
CN120838187A
Graphene-based conductive film and preparation method and application thereof
CN121862523A